2017
DOI: 10.1038/s41598-017-11440-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Akt-mTOR, ubiquitin-proteasome and autophagy-lysosome pathways in locomotor and respiratory muscles during experimental sepsis in mice

Abstract: Sepsis induced loss of muscle mass and function contributes to promote physical inactivity and disability in patients. In this experimental study, mice were sacrificed 1, 4, or 7 days after cecal ligation and puncture (CLP) or sham surgery. When compared with diaphragm, locomotor muscles were more prone to sepsis-induced muscle mass loss. This could be attributed to a greater activation of ubiquitin-proteasome system and an increased myostatin expression. Thus, this study strongly suggests that the contractile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 66 publications
3
19
0
1
Order By: Relevance
“…Autophagy can be triggered through multiple interconnected pathways, such as the MAPK, PI3K-AKT-mTOR and ATP-AMPK-mTOR signaling pathways 32 , 33 . MAPK signaling pathways have a vital role in interfering with autophagy in several types of cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can be triggered through multiple interconnected pathways, such as the MAPK, PI3K-AKT-mTOR and ATP-AMPK-mTOR signaling pathways 32 , 33 . MAPK signaling pathways have a vital role in interfering with autophagy in several types of cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The current study indicates that in the CLP‐induced model of sepsis in mice, DIA fiber atrophy is transient, lasting 24 h after sepsis is initiated, and TA fiber atrophy is sustained, lasting 96 h. These results suggest that the DIA is less sensitive than the TA to the inhibitory effects of CLP‐induced sepsis on fiber size and are in accordance with the work of Prentice et al (), who concluded that the ventilatory muscles are relatively spared from the damaging effects of sepsis in comparison to the limb muscles. Several other studies using the CLP model of sepsis in rats and mice give added weight to this view in that they demonstrate that oxidative stress levels, protein breakdown, and fiber atrophy are significantly lower in the DIA than in limb muscles (Tiao et al, ; Morel et al, ; Stana et al, ; Talarmin et al, ). The mechanisms involved in the relative resistance of the DIA to sepsis‐induced fiber atrophy in our model remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for comparing the diaphragm to a limb muscle was to determine whether myofibrillar proteins in the ventilatory muscles are differentially less sensitive to the adverse effects of sepsis as compared to limb muscles due to their more sustained activity level. We hypothesize, based on previous studies in septic humans and experimental animals, that myofibrillar protein levels in the ventilatory muscles are relatively spared from the inhibitory effects of sepsis in comparison to the limb muscles (Tiao et al, 1997;Morel et al, 2017;Stana et al, 2017;Talarmin et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Studies [ 33 , 34 , 35 ] have shown that autophagy regulates the intracellular homeostatic mechanism that mediates protein and organelle degradation. Autophagy can be induced through multiple interconnected pathways, such as the MAPK, PI3K-AKT-mTOR, and ATP-AMPK-m TOR signaling pathways [ 36 , 37 ]. In our study, the immunofluorescence analyses show that as ZEA concentration increased, the LC3 accumulation in SCs significantly increased and the number of acidic vesicles increased ( Figure 3 C).…”
Section: Discussionmentioning
confidence: 99%